2019
DOI: 10.1111/joim.12944
|View full text |Cite
|
Sign up to set email alerts
|

Dilated cardiomyopathy: from epidemiologic to genetic phenotypes

Abstract: Reichart D, Magnussen C, Zeller T, Blankenberg S (University Heart Center Hamburg, Hamburg, Germany). Dilated cardiomyopathy: from epidemiologic to genetic phenotypes. J Intern Med 2019; 286: 362-372.Dilated cardiomyopathy (DCM) is characterized by left ventricular dilatation and, consecutively, contractile dysfunction. The causes of DCM are heterogeneous. DCM often results from myocarditis, exposure to alcohol, drugs or other toxins and metabolic or endocrine disturbances. In about 35% of patients, genetic mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
140
0
17

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 144 publications
(158 citation statements)
references
References 95 publications
1
140
0
17
Order By: Relevance
“…DCM is a common cause of HF and cardiac transplantation in young adults, with an estimated prevalence of 1:2500 and up to 1:250-400 [30][31][32], and is characterized by ventricular dilatation and contractile dysfunction. While it is clear that DCM can be determined by both genetic and non-genetic factors, the mechanisms underlying its development remain poorly understood.…”
Section: Dilated Cardiomyopathymentioning
confidence: 99%
“…DCM is a common cause of HF and cardiac transplantation in young adults, with an estimated prevalence of 1:2500 and up to 1:250-400 [30][31][32], and is characterized by ventricular dilatation and contractile dysfunction. While it is clear that DCM can be determined by both genetic and non-genetic factors, the mechanisms underlying its development remain poorly understood.…”
Section: Dilated Cardiomyopathymentioning
confidence: 99%
“…To elucidate the possible genetic mechanisms of KD pathogenesis, a dilated cardiomyopathy, rare variants of DCM-causative genes were measured in accordance with minor allele frequency (MAF) below 0.1% in the ExAC and the database for the 1000 Genomes Project [12,13]. There are various rare variants of DCM-causative genes in KD patients as follows: 34 rare variants in TTN (n = 34), 20 in OBSCN (n = 20), 4 in LAMA4 (n = 4), 2 in MYBPC3 (n = 2), 2 in VCL (n = 2), 3 in FHL2 (n = 3), 3 in ZBTB17 (n = 3), 2 in RBM20 (n = 2), 2 in ANKRD1 (n = 2), 2 in KCNQ1 (n = 2), 4 in DMD (n = 4), 2 in MYPN (n = 2), x in MYH7 (n = 2), 2 in BRAF (n = 2), 4 in FLNC (n = 4), 1 in MYH6 (n = 1), 3 in SYNM (n = 3), 2 in RYR2 (n = 2), 1 in ABCC9 (n = 1), 1 in DSC2 (n = 1), 1 in FKRP (n = 1), 1 in FKTN (n = 1), 2 in LDB3 (n = 2), 2 in SCN5A (n = 2), 1 in TXNRD2 (n = 1), 1 in SOS1 (n = 1), 1 in MURC (n = 1), 1 in DSG2 (n = 1) as shown in Supplementary Table S2 and Figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…The effective treatments used in KD are not available so far. Fortunately, an in-depth understanding of the molecular mechanisms underlying DCM opens the door to explore Keshan disease [12,13]. As for KD, we identified various DCM-causative genes, encoding for diverse proteins of the sarcomere ( MYH6, MYH7, MYBPC3 , and MYPN ), cytoskeleton ( TTN, ACTN2, LDB3, SYNM, DMD, FHL2, FKTN, VCL, FLNC, MURC , and NEBL ), desmosomes ( DSP, DSC2, DSG2, PKP2 , and CTNNA3 ), nucleus ( RBM20, ANKRD1, PRDM16, ZBTB17, ALPK3 , and LRRC10 ), ion channel ( SCN5A, ABCC9 , and KCNQ1 ), extracellular matrix ( LAMA2 , and LAMA4 ), and mitochondria ( TXNRD2 ).…”
Section: Discussionmentioning
confidence: 99%
“…), trauma, and endocrine and metabolic disorders 101112 . The incidence of DCM is reported to be 5-7 cases per 100 000 people per year 13 . Previous reports revealed that the prevalence of DCM was 36.5 cases per 100,000 people per year 14 .…”
Section: Introductionmentioning
confidence: 99%